2021
DOI: 10.3390/jcdd9010005
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Complexity of Early Heart Progenitor Cells

Abstract: Early heart development depends on the coordinated participation of heterogeneous cellsources. As pioneer work from Adriana C. Gittenberger-de Groot demonstrated, characterizing thesedistinct cell sources helps us to understand congenital heart defects. Despite decades of researchon the segregation of lineages that form the primitive heart tube, we are far from understanding itsfull complexity. Currently, single-cell approaches are providing an unprecedented level of detail oncellular heterogeneity, offering n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 136 publications
(161 reference statements)
0
9
0
Order By: Relevance
“…established the normal developmental programmes or trajectories of cells left undisturbed. These studies showed that cells gastrulating from the HH3 chicken primitive streak and settling in a position lateral to the boundary of the overlying neural plate will deliver the primitive heart that starts beating at HH10 ((Camp et al, 2012; Garcia-Martinez and Schoenwolf, 1993); reviewed in (Sendra et al, 2021; Wittig and Münsterberg, 2020)). In contrast, cells that settle in a paraxial position contribute to the skull and to craniofacial skeletal muscles (reviewed in (Schubert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…established the normal developmental programmes or trajectories of cells left undisturbed. These studies showed that cells gastrulating from the HH3 chicken primitive streak and settling in a position lateral to the boundary of the overlying neural plate will deliver the primitive heart that starts beating at HH10 ((Camp et al, 2012; Garcia-Martinez and Schoenwolf, 1993); reviewed in (Sendra et al, 2021; Wittig and Münsterberg, 2020)). In contrast, cells that settle in a paraxial position contribute to the skull and to craniofacial skeletal muscles (reviewed in (Schubert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The vertebrate head mesoderm is the first embryonic mesoderm type to emerge during gastrulation (Camp et al, 2012; Garcia-Martinez and Schoenwolf, 1993). It delivers the heart (reviewed in (Meilhac and Buckingham, 2018; Sendra et al, 2021; Spater et al, 2014)), the great vessels (Paffett-Lugassy et al, 2013; Wang et al, 2017), the smooth muscle collar of the cardiac outflow (Wang et al, 2017), genuine craniofacial and oesophageal skeletal muscles (reviewed in (Schubert et al, 2018)) and parts of the skull ((Jandzik et al, 2015); reviewed in (Kuratani, 2005)), with cardiac cells originating from the lateral, and skeletal muscle and also bone/cartilage mainly from the paraxial region of the tissue (reviewed in (Evans and Noden, 2006)). The primitive heart, blood and vascular system are the first fully functional organs in the embryo, and defects in their development are incompatible with life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These progenitor states and their lineage contributions have been studied using single-cell omics approaches in mouse embryonic tissues, as reviewed recently (Lescroart & Zaffran, 2022;Sendra et al, 2021;Tyser, 2023). The lineages of the FHF primarily populate the left ventricle and part of the atria.…”
Section: Introductionmentioning
confidence: 99%